IDENTIFIKASI TELUR CACING SOIL TRANSMITED HELMINT (STH) PADA SISWA SDN 3 ANJIR SERAPAT TENGAH KECAMATAN KAPUAS TIMUR - Ambo Febri Hana NS; Rizqi Perdani; Hafiz Al Farizi; Hajrah Hidriya (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2025)
Worm infection is a disease caused by parasitic worms. The occurrence of worm infections worldwide is very high, with 1.5 billion people, or about 24%. Worm infections in Indonesia especially affect children aged around 1-12 years, caused by Soil Transmitted Helminth (STH), which are worms that require soil to live and use soil as a disease transmission agent. Species of Soil Transmitted Helminth (STH) include Ascaris lumbricoides (roundworm), Trichuris trichiura (whipworm), and hookworm. SDN 3 Anjir Serapat Tengah, located in the East Kapuas sub-district, is a school with a dirt courtyard where many students play barefoot. Additionally, the area often experiences flooding, and no worm infection examinations have ever been conducted there. The purpose of this study is to determine the presence of Soil Transmitted Helminth (STH) egg infections among the students of SDN 3 Anjir Serapat Tengah in the Kapuas Timur District. The method used in this research is the native method. This study is descriptive quantitative in nature. The sampling technique used is total sampling. The results of the study from 23 samples of students at SDN 3 Anjir Serapat Tengah in the Kapuas Timur District indicate that there are no Soil Transmitted Helminth (STH) egg infections. Keywords: Soil Transmitted Helminth, Native Method